2005
DOI: 10.1097/01.aog.0000152000.71369.bd
|View full text |Cite
|
Sign up to set email alerts
|

First-Trimester Intrauterine Hematoma and Outcome of Pregnancy

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
1
8

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 24 publications
2
65
1
8
Order By: Relevance
“…From Ruysch's description, it seems very likely that the latter was the case. Although not mentioned as such it seems certain that the fetus died long before birth, considering the gestational discrepancy, the hydropic degeneration of the umbilical cord, and the placental hemorrhage, which in first trimester pregnancies has an increased risk of fetal death [Maso et al, 2005]. …”
Section: Discussionmentioning
confidence: 99%
“…From Ruysch's description, it seems very likely that the latter was the case. Although not mentioned as such it seems certain that the fetus died long before birth, considering the gestational discrepancy, the hydropic degeneration of the umbilical cord, and the placental hemorrhage, which in first trimester pregnancies has an increased risk of fetal death [Maso et al, 2005]. …”
Section: Discussionmentioning
confidence: 99%
“…Subchorionic hematomas (SCHs) usually appear as hypoechoic or anechoic crescent-shaped areas on ultrasonography. Although the exact etiology is uncertain, they are believed to result from partial detachment of the chorionic membranes from the uterine wall (7). Uterine malformations, history of recurrent pregnancy loss, and infections are the possible predisposing factors (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…However, we did not perform CVS in large ( 1 50% gestational sac circumference) SCH. Maso et al [15] reported that the presence of smalland medium-sized SCH (up to 10 ml) did not increase the spontaneous fetal loss rate. They evaluated the complications of SCH and documented their significance if diagnosed before 9 weeks of gestation.…”
Section: Discussionmentioning
confidence: 95%
“…The volumes of the hematomas were estimated by measuring the maximum transverse, anteroposterior and longitudinal diameters, multiplying these values by a constant of 0.523 [18] . Based on the hematoma volume classification reported by Maso et al [15] , three groups were defined ( ! 1 ml, 1-10 ml, 1 10 ml).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation